2021
DOI: 10.1021/acs.energyfuels.1c01831
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fracture Characteristics on Spontaneous Imbibition in a Tight Reservoir

Abstract: Horizontal well fracturing technology is widely used in the development of shale gas resources. After the fracturing operations, natural and artificial fractures exist in the reservoir at the same time, which has significant effects on spontaneous imbibition to increase shale gas production. Based on nuclear magnetic resonance technology, this work studies the spontaneous imbibition property of fractured shale, including artificial and natural fractures, surface cemented minerals, boundary conditions, etc. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
(69 reference statements)
0
11
1
Order By: Relevance
“…Regarding the imbibition rates across forced imbibitions, they are not much different in these boundaries, which may be due to the approximate porosity, permeability, and total imbibition volume of these four parallel samples. 32,33 Moreover, the values of imbibition potential are such that TSO > ASO > HSO > OSO, illustrating the different contributions made by late imbibition stages to the whole forced imbibition process. However, these findings are contrary to the previous studies, 31,32,59 which can be attributed to the intrinsic differences of imbibition mechanisms between spontaneous imbibition and forced imbibitions coupled with the boundaries.…”
Section: Comparison Of the Imbibition Parameters Of Four Boundariesmentioning
confidence: 95%
See 3 more Smart Citations
“…Regarding the imbibition rates across forced imbibitions, they are not much different in these boundaries, which may be due to the approximate porosity, permeability, and total imbibition volume of these four parallel samples. 32,33 Moreover, the values of imbibition potential are such that TSO > ASO > HSO > OSO, illustrating the different contributions made by late imbibition stages to the whole forced imbibition process. However, these findings are contrary to the previous studies, 31,32,59 which can be attributed to the intrinsic differences of imbibition mechanisms between spontaneous imbibition and forced imbibitions coupled with the boundaries.…”
Section: Comparison Of the Imbibition Parameters Of Four Boundariesmentioning
confidence: 95%
“…The results discussed above are consistent with the recognition of other scholars. 24,32,57 For ASO imbibition, a radial imbibition occurs on the cylindrical side, and a linear imbibition occurs on two ends. The radial imbibition on the cylinder side meets the linear flow on the two end faces and interferes with each other in the forced imbibition process.…”
Section: Comparison Of the Imbibitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Illite can form various crystal structures, among which bundles and fibers can absorb water and expand, causing the most significant damage to pores. Swelling of the I/S interlayer will lead to the disintegration and migration of clay minerals, block the pores and throats, and worsen the reservoir’s physical properties. , Wang et al found that shale pore connectivity is significant for shale oil enrichment and development. Micropore connectivity is the largest, followed by mesopores and macropores.…”
Section: Introductionmentioning
confidence: 99%